PENGARUH METODE SCRAMBLE. TERHADAP KEMAMPUAN MENYUSUN KALIMAT ANAK TUNARUNGU.KELAS V DI SLB BAITURRAHMAN - Windarti Pebriani; Mustafa Mustafa; Syamsuddin Syamsuddin (JURNAL ORTO DIDAKTIKA, 2023)
The problem in this research is the lack of ability to compose sentences in the fifth grade Deaf children at Baiturrahman Special School. The formulation of the problem in this study is 1) How is the application of the scramble method to the fifth grade deaf children at Baiturrahman Special School? 2) How is the ability to compose sentences for the fifth grade deaf children at Baiturrahman Special School? 3) What is the effect of the application of the scramble method to improve sentence construction in the fifth grade deaf children at Baiturrahman Special School?. The purposes of this study are 1) Description of the ability to compose sentences for deaf children in class V at Baiturrahman Special School before using the scramble method. 2) Description of the ability to compose sentences for deaf children in class V at Baiturrahman Special School after using the scramble method. 3) Improved sentence structure for the fifth grade Deaf Children at Baiturrahman Special School through the use of the scramble method. This research is a quantitative research and descriptive type of research, which is to describe the improvement in the ability to compose sentences before and after the application of using the scramble method to the fifth grade deaf students at Baiturrahman Special School. The data collection technique used is an action test technique. The subject in this study was a deaf student in class V. Descriptive analysis technique. The results showed 1) The ability to compose sentences for deaf students before using scramble was in the very poor category, 2) The ability to compose sentences for deaf students after using scramble was in the good category, 3) There was an increase in the ability to compose sentences for deaf students after the application of the scramble method.